Proceedings of the 38th Conference on Design Automation - DAC '01 2001
DOI: 10.1145/378239.379069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of on-chip inductance effects using a novel performance optimization methodology for distributed RLC interconnects

Abstract: This work presents a new and computationally efficient performance optimization technique for distributed RLC interconnects based on a rigorous delay computation scheme. The new optimization technique has been employed to analyze the impact of line inductance on the circuit behaviour and to illustrate the implications of technology scaling on wire inductance. It is shown that reduction in the driver capacitance and output resistance with scaling makes deep submicron (DSM) designs increasingly susceptible to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…However, computing the response in the time domain is analytically intractable. The above transfer function is therefore approximated by a second order Padé approximation as (2) where The 50% delay is given by This transfer function can be used to calculate the 50% delay [16]. Long VLSI interconnects are typically broken up into buffered segment of equal lengths and driven by identical repeaters.…”
Section: Appendix Critical Inductancementioning
confidence: 99%
See 3 more Smart Citations
“…However, computing the response in the time domain is analytically intractable. The above transfer function is therefore approximated by a second order Padé approximation as (2) where The 50% delay is given by This transfer function can be used to calculate the 50% delay [16]. Long VLSI interconnects are typically broken up into buffered segment of equal lengths and driven by identical repeaters.…”
Section: Appendix Critical Inductancementioning
confidence: 99%
“…For minimum total delay in these long interconnects, the delay per unit length in the optimally buffered segment should be minimized. The driver size and interconnect length can be numerically optimized to give minimum delay per unit length [16], [17].…”
Section: Appendix Critical Inductancementioning
confidence: 99%
See 2 more Smart Citations
“…Using the ABCD parameters of a uniform distributed RLC line, It can be shown that the input-output transfer function can be approximated by a second order transfer function as discussed in [5]. ( 1) where…”
Section: Preliminariesmentioning
confidence: 99%